Stakeholders present in organizational mission: an analysis by sector and source of shareholder control - Lugoboni, Leonardo Fabris; Goto, Melissa Midori Martinho (Revista de Administração da UFSM, 2018)
The study aimed to identify: a) stakeholder present on explicit/declared form in Mission Statements; b) emphasis of certain Stakeholder considering the sector of business activity; c) emphasis on certain stakeholders when considering the origin of the shareholder control. For that, supported on the Theory and Management of Stakeholders and Business Strategy, through a documentary study examined the organizational mission of 500 Brazilian companies. The research results indicate that: (i) it is important to consider and analyze stakeholders taking into account the business sector to which they relate, and (ii) that the origin of the stock control seems to be an element to be considered in policy and management of stakeholders.